(1/6)(8x-7)=(x+7)/12

Simple and best practice solution for (1/6)(8x-7)=(x+7)/12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (1/6)(8x-7)=(x+7)/12 equation:


x in (-oo:+oo)

(1/6)*(8*x-7) = (x+7)/12 // - (x+7)/12

(1/6)*(8*x-7)-((x+7)/12) = 0

1/6*(8*x-7)+(-1*(x+7))/12 = 0

(1/6*12*(8*x-7))/12+(-1*(x+7))/12 = 0

1/6*12*(8*x-7)-1*(x+7) = 0

15*x-21 = 0

(15*x-21)/12 = 0

(15*x-21)/12 = 0 // * 12

15*x-21 = 0

15*x-21 = 0 // + 21

15*x = 21 // : 15

x = 21/15

x = 7/5

x = 7/5

See similar equations:

| x+3+8x=2x-1 | | 5y+3(y-6)=3(y+2)-2 | | 3x+7=8x-13 | | (1/6)(8x-7)=(x+7/12) | | 2a-5b=38 | | -1(x-12)+2(x+3)=6(x+3) | | 6[9-(-3x-3)]=54x+108 | | P=c+3b+4aforc | | 7(4x-5)-3=28x-38 | | 8z-19=-15+7z | | 9x+8-7(x+1)=6x+4 | | -1(x-12)+2(x+3)=x+3 | | 4x=34+3x-5+7x | | 9x+1=9(x+9) | | 4x+9-67(x+1)=6x+7 | | x^3+3x^2-81x-85=0 | | -(7y+5)-(-6y-8)=0 | | (4/10x)-2x+(8/5)=(4/5) | | x/2-4=x/5-1 | | 87*28/29*4/9 | | 9x+21+x=5+x+5 | | 12+5n=62 | | -3(6x-5)+3=18x+18 | | 5y+8=48 | | 8x+3=8(x+7) | | 11/7=X/6 | | (2-3x)*(2-3x)=8 | | 0.14(y-3)+0.06y=0.10y-0.5 | | 9x+13=5x+89 | | x+18+21x=3x+9 | | x+28+21x=3x+9 | | 16(18m-4)=24m+8 |

Equations solver categories